Analysis of Influence of the Load Plane Combined with Preload on Durability of Bearing - Kaczor, Jaroslaw (Communications - Scientific Letters of the University of Zilina, 2022)
Angular ball bearings are commonly used whenever there is a demand to increase stiffness of a bearing. The aforementioned increase of stiffness can be achieved by obtaining proper preload in bearings. In common belief, preload has a negative consequence: it increases the load of rolling elements, which must lead to lower durability of bearing compared to the situation before the preload use.
Keywords: angular ball bearings; preload; durability of bearing; bearing life